Green synthesis and characterization of Zinc oxide nanoparticle with polyspice extractantioxidant and antibacterial potential against oral pathogens (Advances in Applied Biological Research, 2025)
Because it is environmentally beneficial, the synthesis of metal oxide nanoparticles  utilizing medicinal plants is growing quickly. The polyspice extract made by  soxhlet extraction with ethylacetate is used in this research to create zinc oxide  nanoparticles. GCMS and qualitative phytochimcal analysis were carried out.  ZnONP and extract antioxidant activities were measured and compared to a  standard. Using the disc diffusion approach, an antibacterial experiment was  conducted against oral pathogens. Polyspice was found to include alkaloids,  flavonoids, and phenol. Ten distinct secondary compounds were detected using  GCMS. UV-Vis Spectroscopy analysis was used to describe the synthesized  NPs, with a peak detected at 396-398 nm. SEM with EDX analysis verified the  NPs’ spherical form 30-98 nm and the primary constituents are oxygen and zinc.  At 50–100 µg levels, ZnO NPs inhibition assay on DPPH, metal chelation, and  hydroxyl radical activity demonstrates good inhibition against free radicals. The  ZnONPs that were biosynthesized showed higher antibacterial effectiveness than  the standard at least 25µg, which is equivalent to standard chlorohexidine. The  pattern of the nanoparticles’ antibacterial activity against the chosen bacteria was  P. gingivalis, S. mutans, and Fusobacterium sp. According to the study’s findings,  synthesizing zinc oxide nanoparticles with a spice extract is an economical and  environmentally responsible way to produce green ZnO nanoparticles that have  strong anti-oxidant and anti-microbial properties against oral infections.
Keywords: oral infection; red complex pathogen; Fusobacterium; Zinc nanoparticle; Antibacterial